Willingness to pay for a group and an individual version of the Lifestyle-integrated Functional Exercise program from a participant perspective - Gottschalk, Sophie; König, Hans-Helmut; Schwenk, Michael; Nerz, Corinna; Becker, Clemens; Klenk, Jochen; Jansen, Carl-Philipp; Dams, Judith (BMC public health, 2022)
Perceived benefits of intervention programs from a participant perspective can be examined by assessing their willingness to pay (WTP). Aiming to support decision-makers in their decision to implement a fall prevention program, this study examined (1) the WTP for a group-based and an individually delivered fall prevention program, (2) which factors influence WTP, and (3) whether the WTP exceeds the intervention costs.